Class influence on political attitudes-current political attitudes held by Malay household heads of higher and lower classes of section 16 and 17, Petaling Jaya, Selangor / Hanim Ali - Hanim , Ali (1974)
Much discussion and research had been done on the subject of social class mainly as a result of the assumption that the individual’s position in society bears a significant influence on his attitudes, values and behaviour. Previous studies have shown that social class level is related to political attitudes and voting behaviour of individuals in society.